PENGARUH UKURAN BIJI TERHADAP KEMAMPUAN TANAMAN TUMBUH KEMBALI SETELAH RUSAK AKIBAT HERBIVORI - Erniwati Erniwati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
The objective of the study is to investigate the effect of seed size in the resprouting ability of seedling after being damaged and whether it correlates with the reserve effect. We grew the seedlings of two species of oak, namely Quercus robur and Quercus  petraea from different seed size, in a greenhouse. The seedlings were harvested at different stages; after emergence, at the first shoot fully developed, and after the seedling had re- grown after the initial shoot was clipped. The result showed that: firstly, at the time of full seedling development, large seeds translocated less percentage of reserve from the seed to seedling. After clipping, the seedlings from large seeds translocated additional resources to the seedling. Secondly, although the larger seed has the larger biomass to re-sprout, the total mass invested in re-sprouting proportional with seedling size. We concluded that the seedlings of larger seeds re-sprout better than those of the smaller seeds. However, we did not find the improved performances correlating with the Reserve Effect Theory